Histological and immunohistochemical characteristics of cerebral amyloid angiopathy in elderly dogs - Slađan Nešić; Vladimir Kukolj; Darko Marinković; Ivana Vučićević; Milijan Jovanović (Veterinary Quarterly, 2017)
Background: Cerebral amyloid angiopathy (CAA) is a disorder characterized by amyloid deposition in the wall of cerebral blood vessels. The deposits of amyloid occur frequently in the blood vessels of the frontal, parietal and occipital cortex. Objective: To examine the characteristics of CAA classified according to the Vonsattel scale in elderly dogs histologically and immunohistochemically as well as the semi-quantitative evaluation of the amyloid deposits in the different segments of the brain. Animals and methods: The brains of 36 dogs of different breeds and sexes, which had been routinely necropsied, were used and divided into two groups: dogs from 1 to 5 and 10 to 18 years old. The tissue sections were stained by hematoxylin–eosin, Congo red and immunohistochemically. Results: Amyloid was accumulated in the wall of cerebral blood vessels in 70% of dogs over the age of 10 years predominantly in the frontal cortex. CAA was demonstrated in elderly dogs as follows: in the frontal cortex (n = 19 or 63%), the parietal cortex (n = 12 or 40%), the hippocampus (40%) and the cerebellum (n = 5 or 17%). The deposits of amyloid in the wall of blood vessels detected by Congo red staining were also Aβ1-14 and Aβ1-42 immunohistochemically positive. Most commonly, the amyloid deposits affected a moderate number of blood vessels. The accumulation of amyloid was immunohistochemically revealed in the blood vessel walls as well as in the senile plaques and neurons. Conclusion: The amount of amyloid in the arterial walls increased with age in dogs, whereas the amyloid accumulated in plaques was Congo red negative.